Spectral evolution of X-ray pulsar 4U 1901+03 during the 2019 outburst based on Insight-HXMT and NuSTAR observations - Nabizadeh Armin; Tsygankov Sergey S; Ji Long; Doroshenko Victor; Molkov Sergey V; Tuo Youli; Zhang Shuang-Nan; Lu Fan-Jun; Zhang Shu; Poutanen Juri (EDP SCIENCES S A, 2022)
We report on a detailed spectral analysis of emission from X-ray pulsar 4U 1901+03 using data obtained by the Insight-HXMT and NuSTAR observatories during the 2019 outburst of the source. Thanks to the extensive coverage of the outburst by Insight-HXMT, we were able to investigate the spectral evolution of the source as a function of flux, and compare these results to the previous reports, focusing on the properties of a putative absorption feature at around 10 keV. In particular, we demonstrate that the broadband X-ray continuum of 4U 1901+03 can be well described with a two-component continuum model without an absorption line at 10 keV, which casts doubt on its interpretation as a cyclotron line. The high quality of the data also allowed us to perform both phase-averaged and phase-resolved spectral analyses as a function of luminosity. Finally, we performed a detailed investigation of another absorption feature in the spectrum of the source around 30 keV recently reported in the NuSTAR data. We show that this feature appears to be significantly detected both in phase-averaged and phase-resolved spectra irrespective of the continuum model.